PENGARUH PAJAK DAERAH, PAJAK RETRIBUSI, DAN PAJAK OTONOMI DAERAH TERHADAP PENDAPATAN ASLI DAERAH MALANG RAYA - Wijayanto, Fariz; Sulistyono, Setyo Wahyu (Journal of Financial Economics & Investment, 2024)
This study aims to analyze the influence of regional taxes, retributions, and regional autonomy taxes on the original local government revenue of Malang areas, such as Malang City, Malang Regency, and Batu City in the 2013-2022 periods. This research uses a quantitative approach. The research data was collected using documentation techniques from the Bappeda of Malang City, Malang Regency, and Batu City to explore more detailed data on various aspects, such as local taxes, retributions, regional autonomy taxes, and original local government revenue, in the Malang areas. Data analysis consisted of descriptive statistical analysis, classical assumption test, and multiple linear regression analysi. The results of this study show that local taxes, retributions, and regional autonomy taxes have a significant effect on original local government revenue  of Malang City, Malang Regency, and Batu City.